Cu2In2ZnS5/Gd2O2S:Tb for full solar spectrum photoreduction of Cr(VI) and CO2 from UV/vis to near-infrared light - Liu, Xinjuan (2021)
Full solar spectrum active heterogenous photocatalysis for environmental applications remains highly challenging. Here we report the novel Cu2In2ZnS5/Gd2O2S:Tb (CG) hybrid photocatalysts via a facile solvothermal method for efficient Cr(VI) and CO2 reduction. The narrow band gap energies of the CG hybrid photocatalysts synthesized via a facile solvothermal method show excellent absorption and catalytic activity in the full solar spectrum. High Cr(VI) reduction rate of 90% and CH4 production rate of 57.73 μmol h−1 g−1 are achieved for CG hybrid photocatalyst with 1 wt.% Gd2O2S:Tb. The excellent performance is due to the fact that in the hybrid, Gd2O2S:Tb as cocatalyst, provides more active sites and inhibits the recombination of charge carriers due to the synergetic effect between Cu2In2ZnS5 and Gd2O2S:Tb, consequently improving the photocatalytic reduction activity.